2006
DOI: 10.1590/s0100-204x2006000200003
|View full text |Cite
|
Sign up to set email alerts
|

Características morfo-anatômicas e bromatológicas de folhas de amoreira em relação às preferências do bicho-da-seda

Abstract: Resumo -O objetivo deste trabalho foi avaliar, quantitativamente, as características morfo-anatômicas e bromatológicas das folhas de dez cultivares de amoreira, e estabelecer as relações de preferência do bicho-daseda, por essas cultivares. Foram coletadas as folhas superior (5 a ) e mediana (15 a ) da planta, contadas a partir do ápice. As cultivares foram comparadas pelos métodos estatísticos multivariados de análise de agrupamento e análise de componentes principais. As cultivares Korin, Calabresa, IZ 5/2 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
2
5
0
3
Order By: Relevance
“…Em amoreira, altas percentagens de consumo de lagartas alimentadas com as cultivares Korin, Calabresa, IZ 5/2 e IZ 15/7 por B. mori foram relacionadas a características desejáveis das folhas, tais como, menor teor de fi bra bruta, menor quantidade de idioblástos de cistólito e de mucilagem, menor porção da epiderme e maior de parênquima (Okamoto & Rodella 2006). Outro fator que pode proporcionar aumento na taxa de consumo pelo inseto é a utilização de alimento nutricionalmente inadequado (Waldbauer 1968).…”
Section: Taxa De Consumo Relativo (Tcr)unclassified
“…Em amoreira, altas percentagens de consumo de lagartas alimentadas com as cultivares Korin, Calabresa, IZ 5/2 e IZ 15/7 por B. mori foram relacionadas a características desejáveis das folhas, tais como, menor teor de fi bra bruta, menor quantidade de idioblástos de cistólito e de mucilagem, menor porção da epiderme e maior de parênquima (Okamoto & Rodella 2006). Outro fator que pode proporcionar aumento na taxa de consumo pelo inseto é a utilização de alimento nutricionalmente inadequado (Waldbauer 1968).…”
Section: Taxa De Consumo Relativo (Tcr)unclassified
“…Leaves of SK4 were found to have a higher nutrient content and were therefore better for feeding the larvae, providing good digestibility and a higher growth rate, as well as a relatively low consumption rate and metabolic cost. A study evaluating the morpho-anatomical features of leaves of different mulberry cultivars fed to domestic silkworms found that higher amounts of idioblasts, cystoliths, and epidermis, as well as a lower proportion of parenchyma, were the least desirable characteristics (Okamoto and Rodella, 2006). Leaves of the loquat Eriobotrya japonica Lindl., another member of the family Rosaceae, have unicellular non-glandular trichomes on both surfaces (abaxial and adaxial), as well as idioblasts containing calcium oxalate crystals, mucilage, and phenolic compounds (Souza et al, 2003).…”
Section: Larval Development On Two Blackberry Cultivarsmentioning
confidence: 99%
“…The mulberry leaf is composed primarily of water, proteins, carbohydrates, vitamins, sterols, and minerals. The caterpillars of silkworm obtain the nutrients from the mulberry leaves to build up the body, sustain life, form cocoons, and reproduce [2,8]. Meeting nutritional requirements through food consumption has a direct impact on the gene expression of characteristics such as weight of the caterpillar and the cocoon, quantity and quality of the silk, and reproductive characteristics of moths [9].…”
Section: Introductionmentioning
confidence: 99%